Governing our neighbours: participation and conflict in neighbourhood planning. Issue 4 (July 2017) - Vigar, Geoff; Gunn, Susannah; Brooks, Elizabeth
Abstract : This paper examines English neighbourhood planning as a form of communicative practice, and in particular its potential to create spaces for agonistic debate about very-local place futures. The value of an agonistic approach is theoretically clear but the emotions associated with participating in, and moreover directing, planning work in one's own neighbourhood limit the likelihood of such an approach emerging. This can partly be addressed through attention to the resources, skills and attitudes required, particularly among process managers, suggesting a need to promulgate agonistic ideas in planning education and practice while requiring the state to adequately resource such processes.